Spray Gun Calibration - Frederick M. Fishel (EDIS)
PI225, a 3-page illustrated fact sheet by F.M. Fishel, provides step-by-step details for calibrating spray guns used in various pest-control settings. Published by the UF Department of Agronomy, March 2010.